(untitled) (Journal of Nonlinear Modeling and Analysis, 2026)
This paper examines CR-slant warped product submanifolds of the form B ×_f N_θ within a nearly Lorentzian para-Sasakian manifold. Here, B represents a CR-product submanifold, N_θ is a slant submanifold and f denotes the warping function. We establish an inequality relating the squared norm of the second fundamental form to the warping function, considering two cases based on the behavior of the structure vector field. Additionally, the conditions under which equality holds are investigated.